ART THERAPY AND EXPRESSIVE PSYCHOTECHNICS IN THE WORK OF THE CENTER OF CHILDREN'S CREATIVITY AND SCHOOL PSYCHOLOGICAL SERVICE (Pedagogy of Higher and Secondary Education, 2022)
In the article lighted up conception of the use of expressive methods of self-exprossion and art-therapy in educational establishment which included the center of child's creation.
Keywords: psychological health; art-therapy in education